2023
DOI: 10.12998/wjcc.v11.i17.4035
|View full text |Cite
|
Sign up to set email alerts
|

Acknowledging the use of botanicals to treat diabetic foot ulcer during the 21st century: A systematic review

Abstract: BACKGROUND Diabetic foot ulcer (DFU) is a serious health issue of diabetes mellitus that affects innumerable people worldwide. Management and treatment of this complication are challenging, especially for those whose immune system is weak. AIM To discuss the plants and their parts used to heal DFU, along with the mode of their administration in diabetic patients. METHODS The original articles on “the plants for the treatment of DFU” studied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 161 publications
0
2
0
Order By: Relevance
“…73 , 74 However, the safety and effectiveness of this complementary intervention are still challenging. 27 Although recent reviews have investigated the potential impact of administrating herbal preparations on treating DFU, their findings are inconclusive; thus, a more comprehensive evidence‐based study on this topic is crucial. 37 Accordingly, we executed this systematic review with meta‐analysis to augment the previous reviews and provide more evidence for the potential effects of topical application and oral intake of herbal products on treating DFU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 , 74 However, the safety and effectiveness of this complementary intervention are still challenging. 27 Although recent reviews have investigated the potential impact of administrating herbal preparations on treating DFU, their findings are inconclusive; thus, a more comprehensive evidence‐based study on this topic is crucial. 37 Accordingly, we executed this systematic review with meta‐analysis to augment the previous reviews and provide more evidence for the potential effects of topical application and oral intake of herbal products on treating DFU.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 23 , 24 , 25 , 26 Systematic reviews, which are at the top of the clinical evidence hierarchy, have recently addressed the potential effect of herbal products in healing DFU; however, they either focused on metabolites and phytoconstituents of used herbs or synthesized the results of investigations with different study designs, making it difficult to draw a reliable conclusion. 27 , 28 , 29 , 30 On the contrary, reviews that performed a meta‐analysis or comprehensive synthesis included only studies conducted in China or evaluated Chinese Herbal Medicines (CHM), which may limit the generalizability and applicability of their findings. 31 , 32 , 33 , 34 , 35 , 36 , 37 Yet, recent randomized controlled trials (RCTs) performed in different regions have reported inconsistent findings regarding the potential efficacy of herbal medications in healing DFU.…”
Section: Introductionmentioning
confidence: 99%